Response of Dictyostelium discoideum to UV‐C and involvement of poly (ADP‐ribose) polymerase - Mir, H. (Cell Prolif, 2015)
OBJECTIVES: Radiation and chemical mutagens are direct DNA‐damaging agents and ultraviolet (UV) radiation is frequently used in biological studies. Consequent to ozone depletion, UV‐C could become a great challenge to living organisms on earth, in the near future. The present study has focused on the role of poly (ADP‐ribose) polymerase (PARP) during UV‐C‐induced growth and developmental changes in Dictyostelium discoideum, a phylogenetically important unicellular eukaryote. MATERIALS AND METHODS: Dictyostelium discoideum cells were exposed to different doses of UV‐C and PARP activity, and effects of its inhibition were studied. Expression of developmentally regulated genes yakA, car1, aca, csA, regA, ctnA, ctnB, gp24, hspD and dsn were analysed using semiquantitative RT‐PCR. RESULTS: We report that the D. discoideum cells displayed PARP activation within 2 min of UV‐C irradiation and there was increase in NO levels in a dose‐dependent manner. UV‐C‐irradiated cells had impaired growth, delayed or blocked development and delayed germination compared to control cells. In our previous studies we have shown that inhibition of PARP recovered oxidative stress‐induced changes in D. discoideum; however, intriguingly PARP inhibition did not correct all defects as effectively in UV‐C‐irradiated cells. This possibly was due to interplay with increased NO signalling. CONCLUSIONS: Our results signify that UV‐C and oxidative stress affected growth and development in D. discoideum by different mechanisms; these studies could provide major clues to complex mechanisms of growth and development in higher organisms.